The Experience of Conversation and Relation with a Well-Being Chabot: Between Proximity and Remoteness - Wygnańska, Joanna (Qualitative Sociology Review, 2023)
The article concerns the users’ experiences of interacting with well-being chatbots. The text shows how chatbots can act as virtual companions and, to some extent, therapists for people in their daily reality. It also reflects on why individuals choose such a form of support for their well-being, concerning, among others, the stigmatization aspect of mental health problems. The article discusses and compares various dimensions of users’ interactions with three popular chatbots: Wysa, Woebot, and Replika. The text both refers to the results of research on the well-being chatbots and, analytically, engages in a dialogue with the results discussed in the form of sociological (and philosophical) reflection. The issues taken up in the paper include an in-depth reflection on the aspects of the relationship between humans and chatbots that allow users to establish an emotional bond with their virtual companions. In addition, the consideration addresses the issue of a user’s sense of alienation when interacting with a virtual companion, as well as the problem of anxieties and dilemmas people may experience therein. In the context of alienation, the article also attempts to conceptualize that theme concerning available conceptual resources.